THE KEY ALGORITHM OF A MODE-MATCHING TECHNIQUE FOR THE ANALYSIS OF RESONANCE POSTS, TEE, TURNSTILE AND OTHER TYPES OF MULTIPORT JUNCTIONS - A. A. Kirilenko; D. Yu. Kulik; S. A. Steshenko (Радиофизика и электроника, 2016)
While designing waveguide junctions, one of the actual tasks is the development of a mode-matching technique for calculating heterogeneities given in different coordinate systems. This paper presents the method for calculating multiport junction using the fields coupling in radial and rectangular waveguides. We proposed a modification of this method for junctions with several shorted ports. The accuracy and convergence of this method were researched.